From Consumer Experience to Affective Loyalty: Challenges and Prospects in the Psychology of Consumer Behavior 3.0 - Monica Gomez-Suarez (Frontiers Research Topics, 2018)
This research topic for Frontiers in Psychology highlights some of the more relevant changes that have conditioned consumer behavior in recent years-among these, the paradigm shift in marketing is worth emphasizing. Today, the market and the companies are implementing Marketing 4.0; This new marketing approach modifies both the business rules and the channels by changing the way to dialogue, interact and relation with consumers. The present Research Topic brings together 30 studies by 76 authors who analyzed the relevance of consumer behavior changes under this new paradigm, using different theoretical and methodological frameworks. These different papers, mainly constituting original research, examine a variety of sub-topics, including online and mobile environments, value co-creation, internal marketing strategies, and diverse industries and product markets. Given this broad selection of papers, we encourage readers to draw their own conclusions about the complex phenomena of consumer behavior. Our hope is that these different perspectives will cover various gaps in the field and prompt discussion among the audience of Frontiers in Psychology.